Dogs and well-Being : the effect of dogs on well-being and stress among university students - Alda Ægisdóttir 2000- (2023)
Stress is a common issue among college students and interventions involving dogs have been used to reduce stress and improve well-being. This study aimed to investigate the effects of interacting with a dog, named woofalong, on stress and well-being among college students at Reykjavik University. Participants (N = 80) were either in the experimental group (interacted with a dog) or the control group (no intervention). All participants answered a printed questionnaire, which included measures of stress and well-being. The results revealed no significant differences in stress and well-being between the experimental and control groups. However, a significant difference in stress was found between genders, with females reporting higher stress levels compared to males, regardless of the woofalong intervention. Since this study is cross-sectional, no conclusion could be reached, and further study is needed. Streita er algeng meðal háskólanema og inngrip með hunda hafa verið notuð til að draga úr streitu og auka vellíðan. Þessi rannsókn skoðaði áhrif þess að hitta hund, í svokallaðri hundastund, á streitu og vellíðan háskólanema í Háskólanum í Reykjavík. Þátttakendur (N = 80) voru annaðhvort í tilraunahóp (hittu hund) eða samanburðarhóp (ekkert inngrip). Allir þátttakendur svöruðu útprentuðum spurningalista sem innihélt mælingar á streitu og vellíðan. Niðurstöður gáfu engan marktækan mun í ljós hvað varðar streitu og vellíðan á milli tilraunaog samanburðarhóps. Aftur á móti var marktækur munur þegar kom að streitu í sambandi við kyn, stelpur fundu marktækt fyrir meiri streitu en strákar, óháð hundastund. Þar sem þetta var þversniðsrannsókn var ekki hægt að alhæfa um niðurstöðu og frekari rannsóknir þarf á þessu sviði.